Obesity and metabolic dysfunction drive sex-associated differential disease profiles in hACE2-mice challenged with SARS-CoV-2 - Katherine S. Lee; Brynnan P. Russ; Ting Y. Wong; Alexander M. Horspool; Michael T. Winters; Mariette Barbier; Justin R. Bevere; Ivan Martinez; F. Heath Damron; Holly A. Cyphert (iScience, 2022)
Summary: Severe outcomes from SARS-CoV-2 infection are highly associated with preexisting comorbid conditions like hypertension, diabetes, and obesity. We utilized the diet-induced obesity (DIO) model of metabolic dysfunction in K18-hACE2 transgenic mice to model obesity as a COVID-19 comorbidity. Female DIO, but not male DIO mice challenged with SARS-CoV-2 were observed to have shortened time to morbidity compared to controls. Increased susceptibility to SARS-CoV-2 in female DIO was associated with increased viral RNA burden and interferon production compared to males. Transcriptomic analysis of the lungs from all mouse cohorts revealed sex- and DIO-associated differential gene expression profiles. Male DIO mice after challenge had decreased expression of antibody-related genes compared to controls, suggesting antibody producing cell localization in the lung. Collectively, this study establishes a preclinical comorbidity model of COVID-19 in mice where we observed sex- and diet-specific responses that begin explaining the effects of obesity and metabolic disease on COVID-19 pathology.